Sludge holding tanks performance in wastewater treatment: Techno-economic assessment - Hussein, Hossam Mostafa; Ali, Sayed Ismail; Ali, Marwan Mohamed; Elmoamen, Mahmoud Abd (Brawijaya University, 2025)
This study evaluates the performance and economic viability of sludge holding tanks in wastewater treatment, focusing on their role in sludge management, particularly in Egypt’s expanding wastewater infrastructure. Despite their widespread use, sludge holding tanks lack standardized design and operational guidelines. This research addresses this gap by assessing operational parameters, design criteria, and economic impacts, especially for small-scale treatment plants. A pilot-scale sludge holding tank was tested in two phases: the first examined the effects of retention time and air mixing rates on waste-activated sludge (WAS) treatment, while the second investigated the impact of increased solids loading by adding primary sludge. Results indicate that sludge holding tanks primarily function as thickening units, with optimal performance at retention times of 23-26 hours and air mixing rates of 1.3-6 m³/hr/m³. Lower air mixing rates improved thickening efficiency, achieving dry solids content of up to 1.5%, suitable for dewatering. The addition of primary sludge further enhanced thickening, underscoring the importance of sludge composition. Economically, these tanks are more cost-effective than traditional thickeners and digesters, requiring less volume and lower operational costs. Although effluent quality may not match advanced treatment units, their simplicity and affordability make them ideal for small-scale facilities. The study provides practical recommendations for optimizing sludge holding tanks, contributing to more sustainable and efficient sludge management strategies.